The Development of Students’ Worksheets Face to Face Online Based on Hypercontent on Temperature and Heat Topic - Khaeruddin Khaeruddin; Rahmawati Rahmawati; Nurfazlina Nurfazlina; Salwa Rufaida; Nurhayati Nurhayati (Postgraduate, University of Mataram, 2022)
The 21st century is a century that encourages humans to integrate life with ICT and education is no exception. However, in reality, in SMA Muhammadiyah 1 Unismuh Makassar, the use of technology such as mobile phones and the use of teaching materials is still lacking. Therefore, one of the efforts made is to produce hyper-content based LKPD student worksheet so that students are more interested in learning physics. This study aims to describe the content validity of hyper-content student worksheet on temperature and heat topic. Furthermore, the goals of this research was to describe the practicality of the response of teachers and students to hyper-content based student worksheet on the temperature and heat topic, and describe the effectiveness of student worksheet for the given questions. This research is a type of development research (R&D) using the ADDIE model design (analysis, design, development, implementation, and evaluation). The results showed that the feasibility of hyper-content based student worksheet based on the assessment of valuators 1 and 2 was categorized as very feasible, with the percentage of LKPD validation 96.0%. Teachers and students gave a very positive response to the practicality of the LKPD based on hyper-content- as a learning medium with a teacher response percentage of 100.0% with very practical criteria and student responses 84.37% very practical criteria. The effectiveness obtained from the students' test results of 0.59 criteria is quite effective